Proposta de um índice para avaliação da assistência pré-natal na atenção básica - Silva, Esther Pereira da (2012)
Besides its great impact on the obstetric outcomes and health promotion, the prenatal care helps to identify risky situations for the pregnant woman and fetus, allowing timely interventions. The Kessner Index and the Adequacy of Prenatal Care Utilization Index (APNCU) are the indexes most used by literature to evaluate prenatal care. However, these procedures prioritize only certain quantitative aspects of prenatal care at the expense of its entirety. In this context, this study aimed to propose an instrument, called IPR/Prenatal Index , to evaluate prenatal care in a more comprehensive way, based on the guidelines of the Humanization of Prenatal and Birth Program (PHPN) of Brazil s Ministry of Health. The study carries out a comparative analysis with the other indexes already validated. This instrument combines, in a single procedure, new quanti-qualitative elements related to infrastructure, work process and prenatal assistance outcomes in the context of the primary health care services and its users. According to this instrument, prenatal is classified in: upper adequate , adequate , intermediate and inadequate . The cross-sectional study was conducted in the city of João Pessoa in 44 Basic Health Units represented by professionals directly involved in prenatal care, and 238 users among pregnant/postpartum women and mothers of newborns up to six months old. In order to verify the consistency of the proposed instrument we carried out an internal comparative analysis of its prenatal adequacy categories with the Kessner and APNCU indexes, based on the calculation of the odds ratio, when associated with adverse birth outcomes indicative of inadequacy of prenatal care. For all these indexes, we considered the category adequate as reference. When compared to the other indexes, the IPR/Prenatal index proved to be internally consistent when associated with outcomes such as prematurity, insufficient birth weight and non-exclusive breastfeeding, with the highest adequacy category being a protection factor from the occurrence of these negative outcomes; We conclude, therefore, that using a more comprehensive index to evaluate and classify the prenatal care as adequate is effective, since it shows the association with the lower occurrence of adverse obstetric outcomes, confirming that the quality of care can be achieved through extensive elements that go beyond the number of appointments and the outset of prenatal care, as the other indexes recommend.